Legal Aspects of Regulatory Treatment of Banks in Distress - Asser, T. (Washington, D.C. : International Monetary Fund, 2001)
This book analyzes and compares the laws of selected industrial countries that are representative of the different approaches to the treatment of banks in distress. It addresses only those banking and economic policy issues that are required for a proper understanding of the banking law or the legal strategies, procedures, and practices that have evolved in the treatment of banking problems. The book does not cover international aspects of bank insolvency, but rather has a domestic focus, given that bank regulation and supervision are still largely a national endeavor.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet